Hubungan Pelaksanaan Rawat Gabung dengan Keberhasilan Menyusui di Masa Pandemi Covid 19 di Wilayah Kerja UPTD Puskesmas Bawomataluo - Debora Paninsari; Meilindasari Zandroto; Veronica Tiolenti Tambunan; Tasya Pratiwi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The background problem in this study is that follow-up care provides an opportunity for mothers to be close to their babies, which makes the mother have strong desires and motivations, so that the frequency of mothers giving breast milk will be more often so that the success of exclusive breastfeeding can be achieved. The purpose of the study was to find out the relationship of the implementation of treatment joining the success of breastfeeding in the covid-19 pandemic in The Health Center Bawomataluo Fanayama District of South Nias Regency. Value of P-value 0,007<Alpha (0,05). Have relationship of the implementation of treatment joining the success of breastfeeding in the covid-19 pandemic in The Health Center Bawomataluo Fanayama District of South Nias Regency.